A Semantic Analysis of Meaning Construction in the Cinderella Story Through Contextual Interpretation - Cindy Debora Manurung; Bernieke Anggita Ristia Damanik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates the construction of meaning in the Cinderella narrative through contextual interpretation using a semantic approach. The research responds to the growing scholarly interest in examining literary narratives as complex semiotic structures in which meaning emerges through the interaction between language, symbolism, and contextual interpretation rather than through isolated lexical definitions. Employing a non-empirical qualitative design grounded in textual and semantic analysis, the study utilizes the Cinderella narrative published by World Stories as its primary data source. The analysis focuses on lexical meaning, contextual meaning, and implicit meaning identified within narrative descriptions, dialogues, symbolic objects, and situational structures. The findings reveal that lexical expressions associated with domestic labor, transformation, and social hierarchy construct broader ideological meanings concerning oppression, legitimacy, identity, and moral recognition. Contextual interpretation demonstrates that spatial settings, interpersonal relations, and temporal structures significantly influence semantic understanding within the narrative. Symbolic elements such as the glass slipper and magical transformation generate implicit meanings related to resilience, social mobility, and validation. The study confirms that semantic analysis integrated with contextual interpretation provides an effective framework for uncovering multilayered meanings embedded within literary discourse.